Evaluating the Change Process of a Brief Cognitive Behavior Therapy Workshop for Psychological Distress Among Primary Care Self-Referrals in Selangor, Malaysia - Sam, Jeng Mun; Ismail, Siti Irma Fadhilah; Tan, Kit-Aun; Sidik, Sherina Mohd; Osman, Zubaidah Jamil (Frontiers in Psychiatry, 2022)
Despite the high prevalence of psychological distress in primary care, only a limited number of individuals can benefit from early and evidenced-based psychological approach. Barriers to help-seeking attributable to stigma, lack of proper care pathway to evidenced-based psychological interventions, and high volume of primary care attendees are among the factors that contribute to the inadequate psychological treatments. This study examined the implementation of change process using a brief cognitive behavioral therapy (b-CBT) workshop as a potential approach in managing psychological distress among 73 primary care self-referrals using purposive sampling. One-way repeated measures multivariate analysis of variance was used to analyze changes in psychological distress within a non-randomized quasi-experimental study. Results revealed significant differences in psychological distress using Depression, Anxiety, and Stress Scale-21 items at three time-points (pre-intervention, post-intervention, and one-month follow-up). The b-CBT workshop implementation showed positive changes for psychological distress, suggesting the possibility of integrating brief, non-stigmatized, and evidenced-based psychological approach in the primary care level. However, the self-referral characteristics of the attendees remained unknown. Potential feasibility, participant’s usability and satisfaction, and implementation of b-CBT workshop to improve psychological distress can be found in this study.